Experimental infection of Phlebotomus perniciosus and Phlebotomus tobbi with different Leishmania tropica strains. Issue 11 (October 2019) - Vaselek, Slavica; Volf, Petr
Graphical abstract: Highlights: Laboratory-reared Phlebotomus tobbi and Phlebotomus perniciosus are highly susceptible to Leishmania tropica . Metacyclic forms and colonisation of the stomodeal valve were observed in both sand fly species. This is the first known experimental study showing high vector competence of P. tobbi for L. tropica . Infection parameters of L. tropica are higher than in the natural vector Phlebotomus sergenti . Phlebotomus tobbi and P. perniciosus may play a role in L. tropica transmission in nature. Abstract: Cutaneous leishmaniasis due to Leishmania tropica is increasingly documented in Europe and the Middle East. Besides its specific vector, Phlebotomus sergenti, permissive Phlebotomus sand flies are suspected as potential vectors of L. tropica . We investigated the susceptibility of two widely distributed species, Phlebotomus perniciosus and Phlebotomus tobbi . Laboratory-reared sand flies were infected experimentally with L. tropica strains differing in lipophosphoglycan epitopes, geographical distribution and epidemiology. High infection rates, heavy parasite loads and fully developed late-stage infections including colonization of the stomodeal valve were observed in all parasite-vector combinations. Our findings demonstrate that P. perniciosus and P. tobbi are susceptible to different L. tropica strains and may play a role in their circulation in endemic foci of Europe, the Middle East and North Africa.